2021
DOI: 10.32585/ijimm.v3i1.1401
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Appropriate Selection Learning Media at Junior High School

Abstract: The appropriate selection of learning media can help the process of delivering messages from teachers to students become more effective. The selection of the right learning media requires the use of certain principles and criteria to be precise in choosing a learning medium because each learning medium should have different characteristics and specifications of usefulness. This study aims to conduct a summative evaluation of the appropriate selection of local wetland content learning media in junior high schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…This builds the students understanding of the material. Besides, Corser (2021) [18] for secondary students (teenagers) using media that entertain them in learning particular material since it is easier for them to comprehend it. Both researches have shown that media gives important effect to students' learning.…”
Section: Resultsmentioning
confidence: 99%
“…This builds the students understanding of the material. Besides, Corser (2021) [18] for secondary students (teenagers) using media that entertain them in learning particular material since it is easier for them to comprehend it. Both researches have shown that media gives important effect to students' learning.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, teachers must choose the attractive teaching strategies to increase student participation and achieve learning objectives (Magdalena et al, 2020). In order to achieve learning objectives, every teacher is required to understand the learning strategies that will be applied properly (Mansur & Utama, 2021). Related with this, a teacher must consider the learning strategies used.…”
Section: Introductionmentioning
confidence: 99%